2018
DOI: 10.1002/cnr2.1153
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic analysis identifies factors driving racial disparity in prostate cancer

Abstract: Background Prostate cancer (PCa) is the second most leading cause of death in men worldwide. African‐American men (AA) represent more aggressive form of the disease compared to Caucasian (CA) counterparts. Several lines of evidences suggest that biological factors are responsible for the observed racial disparity. Aim This study was aimed at identifying the epigenetic variation among AA and CA PCa patients and whether DNA methylation differences have an association with clinical outcomes in the two races. Meth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 58 publications
(103 reference statements)
0
7
0
Order By: Relevance
“… 23 , 24 LRP10 gene has also been reported to be hypermethylated in prostate cancer. 25 MGAM is a maltase-glucoamylase, which is an enzyme that plays a role in the digestion of starch. It is reported to have lower mRNA expression in prostate cancer tissues compared to non-tumorous prostate tissues.…”
Section: Resultsmentioning
confidence: 99%
“… 23 , 24 LRP10 gene has also been reported to be hypermethylated in prostate cancer. 25 MGAM is a maltase-glucoamylase, which is an enzyme that plays a role in the digestion of starch. It is reported to have lower mRNA expression in prostate cancer tissues compared to non-tumorous prostate tissues.…”
Section: Resultsmentioning
confidence: 99%
“…Despite heterogeneities in methodology and geographic focus, all 49 studies mirror the growing perception that epigenetic markers, and particularly DNA methylation (98%; along with one including RNA non‐coding, Li et al, 2020 ), are a potential basis for explaining ethnic or race‐based differences in health, disease incidence, aging, or reactions to exposures or drugs (Adkins et al, 2011 ; Barfield et al, 2014 ; Davis Lynn et al, 2019 ; Heyn et al, 2013 ; Li et al, 2020 ; Needham et al, 2015 ; Rai et al, 2019 ; Rawlik et al, 2017 ; Song et al, 2015 ). As one study claims, “DNA methylation diversity is a source of variability in human groups at macro and microgeographical scales” (Giuliani et al, 2016 ; similarly McKennan et al, 2020 ) and, given that it is considered “highly divergent between populations” (Fraser et al, 2012 ) can be used to elucidate variation in biological traits or different effects of environmental exposures on racially defined populations: That is, using the terminology of these studies, African American, European, Caucasians (sic), Hispanic, Chinese, or Western (see Table S1 , column 3 for complete overview).…”
Section: A Scoping Review Of Environmental Epigenetics Dohad and Race...mentioning
confidence: 99%
“…Only three articles (6%) mention or recognize the importance of wider socio‐structural factors as “drivers of racial health differences” (Pepin et al, 2021 ; see also Lynn et al, 2019 , Tsegaselassie et al, 2021 ). Reversibility is explicitly highlighted by 14 articles (28%) but most discussions of this are brief and often limited to the conclusion, with occasional reference to prospective pharmaceutical or therapeutic interventions (Chan et al, 2017 ; Demerath et al, 2015 ; Devaney et al, 2015 ; Enokida et al, 2005 ; Lynn et al, 2019 ; Okosun et al, 2000 ; Pepin et al, 2021 ; Pheiffer et al, 2020 ; Rai et al, 2019 ; Salihu et al, 2016 ; Tajuddin et al, 2019 ; Wang et al, 2016 ; Wiley et al, 2013 ; Zhu et al, 2016 ). v One significant exception is a study by Giuliani et al ( 2016 ) that emphasizes reversibility and variability as a theme throughout the article.…”
Section: A Scoping Review Of Environmental Epigenetics Dohad and Race...mentioning
confidence: 99%
“… 8 , 166 Another interesting study looking at epigenetic differences between AA and CA men found tumors from AA men had hypermethylated loci at MC1, whereas CA men had hypomethylated loci at the MC3 cluster. 167 The result of these epigenetic changes was reduced noncanonical Wnt signaling (Wnt/Ca+2 signaling) in AA men, and activation via the MC3 cluster for CA men. Furthermore, PI3K signaling and inflammatory pathways cause increased expression of MC1 genes.…”
Section: Specific Findings In African American Menmentioning
confidence: 99%
“…Furthermore, PI3K signaling and inflammatory pathways cause increased expression of MC1 genes. 167 Looking at whole blood DNA from AA men, Moses‐Fynn et al 168 assessed DNA methylation status in the genes RARβ2, TIMP3, SPARC, CDH13, HIN1, LINE1, CYB5R2, and DRD2. Overall, they found DNA promoter methylation was more common in AA men, and was linked to a number of clinical and pathological prognostic parameters including Gleason score.…”
Section: Specific Findings In African American Menmentioning
confidence: 99%